Politik Dan Tradisi: Politik Uang Dalam Pemilihan Kepala Desa - Magda Ilona Dwi Putri; Nahdia Arifani; Dela Ratnasari; Maurelia Vidiara Auliavia; Sinta Nuriyah; Agus Mahfud Fauzi (Institute of Social and Political Science Jakarta (Institut Ilmu Sosial dan Ilmu Politik Jakarta - IISIP Jakarta), 2020)
The election of the village head is a democracy celebration for such communities as that in Kedungjati Village. The people of Kedungjati Village have strong ties among themselves so they know the prospective village head on a personal level. However cheating is still often encountered, one of whose elements is the practice of money politics. This study aims to explain the rational actions of the people of Kedungjati Village regarding the acceptance of money politics. The previous election of the candidate for Village Head of Kedungjati was won by the candidate with the least encounters of money politics. This study uses a qualitative approach with observations and interviews. The subjects of this research are the people of Kedungjati Village who accepted money politics when the election for the Village Head of Kedungjati was in progress. The results showed that the act of accepting bribes was based on a utilitarian mindset. People consider money politics as a tradition. The people of Kedungjati Village will come to the TPS with sangu money or money given by the candidates. Money politics is accepted because of the assumption that rejecting luck is not a good thing. Since the beginning, the community has known the motives and goals of the candidates. But on the other hand, society has its own criteria for candidates without coercion put in effect by money politics.